COMPARATIVE ANALYSIS AND RISK ASSESSMENT OF RAINWATER AND BORED WELL WATER AS POTABLE WATER SOURCES IN COASTAL REGIONS - Uun Lestari; Putri Meira Shyiang Sri; Nur Laely (Universitas Mataram, 2026)
Water is a vital resource for coastal communities, which often have limited access to clean water. This study aimed to analyze and compare the quality of rainwater and borehole water as drinking water sources in Sayolo 3, Tanjung Village, South Sorong Regency. This study employed a quantitative descriptive approach. Water samples were collected directly from the sources and analyzed in a laboratory for 12 physical and inorganic chemical parameters. The results were compared with the quality standards stipulated in the Indonesian Minister of Health Regulation Number 2 of 2023. The findings indicate that rainwater meets all tested parameters, including pH, total dissolved solids (TDS), turbidity, iron (Fe), lead (Pb), manganese (Mn), nitrate, and hardness. In contrast, the borehole water contains iron (Fe) at a concentration of 0.309 mg/L, exceeding the maximum permissible limit of 0.2 mg/L, although its other parameters remain within the safe limits. It was concluded that rainwater is more suitable for direct use as a drinking water source in the study area, whereas borehole water requires additional treatment, specifically to reduce iron content, to ensure its safety for consumption.